Viral suppression and adherence among HIV‐infected children and adolescents on antiretroviral therapy: results of a multicenter study - Maria L.S. Cruz; Claudete A.A. Cardoso; Mariana Q. Darmont; Edvaldo Souza; Solange D. Andrade; Marcia M. D'Al Fabbro; Rosana Fonseca; Jaime G. Bellido; Simone S. Monteiro; Francisco I. Bastos (Brazilian Society of Pediatrics, 2014)
Objective: To evaluate treatment adherence among perinatally‐infected pediatric human immunodeficiency virus (HIV) patients followed in pediatric centers in Brazil. Methods: This was a cross‐sectional multicenter study. Medical records were reviewed and adherence scale, assessment of caregivers' quality of life (WHOQOL‐BREF), anxiety, depression, and alcohol/substances use/abuse were assessed. Outcomes included self‐reported 100% adherence in the last three days and HIV viral load (VL) < 50 copies/mL. Statistical analyses included contingency tables and respective statistics, and multivariable logistic regression. Results: 260 subjects were enrolled: 78% children and 22% adolescents; 93% of caregivers for the children and 77% of adolescents reported 100% adherence; 57% of children and 49% of adolescents had VL < 50 copies/mL. In the univariate analyses, HIV diagnosis for screening due to maternal infection, lower caregiver scores for anxiety, and higher scores in physical and psychological domains of WHOQOL‐BREF were associated with 100% adherence. Shorter intervals between pharmacy visits were associated with VL < 50 copies/mL (p ≤ 0.01). Multivariable regression demonstrated that caregivers who did not abuse alcohol/other drugs (OR = 0.49; 95% CI: 0.27‐0.89) and median interval between pharmacy visits < 33 days (OR = 0.97; 95% CI: 0.95‐0.98) were independently associated with VL < 50 copies/mL; whereas lower caregiver scores for anxiety (OR = 2.57; 95% CI: 1.27‐5.19) and children's HIV diagnosis for screening due to maternal infection (OR = 2.25; 95% CI: 1.12‐4.50) were found to be independently associated with 100% adherence. Conclusions: Pediatric HIV programs should perform routine assessment of caregivers' quality of life, and anxiety and depression symptoms. In this setting, pharmacy records are essential to help identify less‐than‐optimal adherence.